Genetic Characterization of Chikungunya Virus Among Febrile Dengue Fever–Like Patients in Xishuangbanna, Southwestern Part of China - Zou, Meng; Su, Chunyan; Li, Tingting; Zhang, Jing; Li, Daiying; Luan, Ning; Ma, Dehong; Liu, Jiansheng; Sun, Qiangming; Peng, Xiaozhong; Liu, Hongqi (Frontiers in Cellular and Infection Microbiology, 2022)
Co-infection of chikungunya virus (CHIKV) has been recently reported during dengue fever epidemics. However, infection of CHIKV is often neglected due to its misdiagnosis as dengue virus infection. In the summer of 2019 when dengue fever was epidemic, we collected 697 serum samples from febrile dengue fever-like patients in Xishuangbanna, southwestern part of China. Dengue virus (DENV) RNA was detectable in 99.42% of these patients. Notably, 88 patients (12.62%) showed the presence of CHIKV RNA, among which 86 patients were co-infected with DENV and CHIKV. We sequenced and analyzed the full genome of CHIKV virus in 4 out of 88 samples (2 CHIKV infected and 2 co-infected). The results suggested that the four strains were all Asian genotype, and had the highest homology (99.4%) with the SZ1239 strain (Accession number MG664851) isolated in 2012 and possibly introduced from Indonesia. Further comparison with the conserved sequences in the whole genome of 25 strains of CHIKV showed that there were 13 and 21 amino acid mutants in structural proteins and non-structural proteins, respectively. The previously reported adaptive mutations of E2-W64R, E2-I211T, E2-K233E, E1-A98T and E1-K211E occurred in the 4 strains of this study. In conclusion, this study reports a co-infection of CHIKV during the DENV epidemic in the city Xishuangbanna, 2019. Molecular epidemiology revealed that CHIKV identified in this study was indigenous and belongs to Asian lineage with lineage-specific mutations and some reported adaptive mutations, which is distinct from the recently reported CHIKV (East/Central/South African) in Ruili, the city next to Xishuangbanna.